1994
DOI: 10.1046/j.1525-1438.1994.04060395.x
|View full text |Cite
|
Sign up to set email alerts
|

Carcinoma of the fallopian tube. A clinical and histopathologic review. The Radiumhemmet series

Abstract: A histopathologic and clinical review of the Radiumhemmet series of primary fallopian tube carcinoma (PFTC) treated from 1923 to 1991 revealed that 128 cases fulfilled the diagnostic criteria for PFTC. These cases were staged according to the new FIGO staging rules for PFTC. Survival was studied with respect to prognostic factors such as age, stage, histologic subgroups, degree of differentiation and mode of treatment. The mean age at diagnosis was 56 years. Seventy-four per cent were found to be in stage Ia-I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
1

Year Published

1999
1999
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(17 citation statements)
references
References 10 publications
0
16
1
Order By: Relevance
“…The most common histological types are shown in Table 2 [50,[71][72][73][74][75]. Serous tumors are graded with respect to their differentiation and extent of solid components: most tumors are poorly differentiated [48,50,71] (Table 3).…”
Section: Pathologymentioning
confidence: 99%
See 1 more Smart Citation
“…The most common histological types are shown in Table 2 [50,[71][72][73][74][75]. Serous tumors are graded with respect to their differentiation and extent of solid components: most tumors are poorly differentiated [48,50,71] (Table 3).…”
Section: Pathologymentioning
confidence: 99%
“…Radiotherapy could possibly be considered either as adjuvant therapy for early-stage patients [2,5,28,45,46,73,85,[93][94][95][96], for stage III residual negative patients, or in the relapse setting. Although radiotherapy has been used traditionally in the past as an adjuvant therapy for PFTC, its role in the era of effective chemotherapy is less well defined and controversial.…”
Section: Radiotherapymentioning
confidence: 99%
“…Staging of the disease in accordance to the FIGO scale and the residual disease after initial surgery are the only, wide-accepted and reliable prognostic factors in PFTC [12, 13, 2123]. The depth of tubal invasion in the cases limited to the fallopian tube [19, 23], and the presence of lymphocytic infiltration have been suggested to play an unfavorable prognostic role in PFTCs.…”
Section: Introductionmentioning
confidence: 99%
“…The depth of tubal invasion in the cases limited to the fallopian tube [19, 23], and the presence of lymphocytic infiltration have been suggested to play an unfavorable prognostic role in PFTCs. The value of other commonly used prognostic factors did not find wider acceptance [12, 13]. They may be used as evidence to support prognosis, but none of them are independent prognostic factors.…”
Section: Introductionmentioning
confidence: 99%
“…10 Studies have reported clustering of breast cancers and PFTC in same patients. 2,11,12 There are also several findings on higher BRCA1 and BRCA2 mutation prevalence among PFTC patients than in average healthy population. [13][14][15][16] The present investigation is a unique multi-centre study including cancer data from 13 population-based cancer registries in Europe, Australia, Canada and Singapore.…”
mentioning
confidence: 99%